2018
DOI: 10.1111/imj.13623
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes in young adults in Central Auckland: demography and complications

Abstract: New migrants, New Zealand-born Pāsifika and patients with mental illness or an intellectual disability comprise the bulk of young onset T2D. The disease is aggressive, and by the age of 40, patients are already developing advanced complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 36 publications
0
11
0
2
Order By: Relevance
“…In Northland, DR prevalence (>R0) was twice as high among people with T2DM (34.6%) compared to people with T1DM (16.7%) . In Auckland, Europeans were the group with the highest prevalence of any DR (43.0%), though no Europeans had sight‐threatening DR, compared to 9.5% of Māori, 8.6% of Pacific and 4.1% of South Asians (Table ). Despite the younger age of participants in these studies, within each ethnicity group, the DR rates were similar to or higher than the rates reported for the broader age groups in other studies (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In Northland, DR prevalence (>R0) was twice as high among people with T2DM (34.6%) compared to people with T1DM (16.7%) . In Auckland, Europeans were the group with the highest prevalence of any DR (43.0%), though no Europeans had sight‐threatening DR, compared to 9.5% of Māori, 8.6% of Pacific and 4.1% of South Asians (Table ). Despite the younger age of participants in these studies, within each ethnicity group, the DR rates were similar to or higher than the rates reported for the broader age groups in other studies (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies reported prevalence of DR disaggregated by ethnicity or within one ethnicity group; five of these also reported sight‐threatening DR (Table ). When reporting DR, three studies presented data only for people with T2DM, four studies did not specify diabetes type, and one reported DR separately for people with T1DM and T2DM.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations